How Listeria monocytogenes Shapes Its Proteome in Response to Natural Antimicrobial Compounds - Lanciotti, Rosalba; Braschi, Giacomo; Patrignani, Francesca; Gobbetti, Marco; De Angelis, Maria (Frontiers in Microbiology, 2019)
The goal of this study was to investigate the adaptation of L. monocytogenes Scott A cells to treatments with sublethal doses of antimicrobials (ethanol, citral, carvacrol, E-2-hexenal and thyme essential oil). The survival of L. monocytogenes cells was not affected by the antimicrobials at the concentrations assayed, with the exception of ethanol (1% v/v) and thyme essential oil (100 mg/L), which decreased cell viability from 8.53 ± 0.36 to 7.20 ± 0.22 log CFU/mL (P=0.04). We subsequently evaluated how L. monocytogenes regulates and shapes its proteome in response to antimicrobial compounds. Compared to the control cells grown under optimal conditions, L. monocytogenes treated for 1 h with the antimicrobial compounds showed increased or decreased (≥ or ≤ 2-fold, respectively; P<0.05) levels of protein synthesis for 223 protein spots. As shown multivariate clustering analysis, the proteome profiles differed between treatments. Adaptation and shaping of proteomes mainly concerned cell cycle control, cell division, chromosome, motility and regulatory related proteins, carbohydrate, pyruvate, nucleotide and nitrogen metabolism, cofactors and vitamins and stress response with contrasting responses for different stresses. Ethanol, citral (85 mg/l) or (E)-2-hexenal (150 mg/L) adapted cells increased survival during acid stress imposed under model (BHI) and food-like systems.